MiR-302 targets PAK5 and prevents the transition from chronic hepatitis B to liver cirrhosis - Zhao, Yi; Liu, Xia; Wang, Lan; Pan, Xiaoyan; Pan, Feng; Ke, Qiang (Journal of the Pakistan Medical Association, 2024)
Objective: To determine and compare the levels of p21-activated kinase 5 messenger ribonucleic acid and micro-ribonucleic acid 302 in the serum of patients with chronic hepatitis B, liver cirrhosis and healthy individuals, and to analyse the roles and correlation of p21-activated kinase 5 messenger ribonucleic acid and micro-ribonucleic acid 302 in the progression of chronic hepatitis. Method: The observational, clinical, case-control study was conducted at the Department of Laboratory Medicine, Affiliated Hospital of Hangzhou Normal University, Hangzhou, China, from February 2021 to January 2022. Peripheral blood serum samples were collected from healthy individuals undergoing physical examinations, as well as from patients with chronic hepatitis B and hepatitis B-related liver cirrhosis. Total ribonucleic acid was isolated and purified using the magnetic bead method, and the relative expression levels of micro-ribonucleic acid 302 and p21-activated kinase 5 messenger ribonucleic acid were determined using quantitative real-time polymerase chain reaction. Clinical test results were retrospectively analysed, and differences between the groups were assessed. Data was analysed using SPSS 22. Results: Of the 70 participants, 18(25.71%) were healthy individuals with median age 33 years (interquartile range: 25-36.25 years), 18(25.71%) were patients with chronic hepatitis B having median age 34 years (interquartile range: 26-42 years), and 34(48.57%) were patients with cirrhosis having median age 54 years (interquartile range: 44-62 years). Overall, there were 50(71%) males and 20(29%) females with mean age 42.7±13.8 years. Median albumin (p=0.0365) and platelet (p=0.0116) levels were significantly lower in cirrhosis group compared to chronic hepatitis B group. Median aspartate aminotransferase level (p=0.0400) and aspartate aminotransferase/platelet ratio (p=0.0053) of chronic hepatitis B group were significantly higher than the healthy group (n=18). The expression of p21-activated kinase 5 was significantly increased in cirrhosis group compared to chronic hepatitis B group (p=0.0444) and healthy controls (p=0.0089). Compared to the healthy individuals, the expression of micro-ribonucleic acid 302 was significantly increased in both chronic hepatitis B (p=0.0237) and cirrhosis groups (p=0.0428). Conclusions: P21-activated kinase 5 represented a promising therapeutic target for liver disease, and micro-ribonucleic acid 302 could serve as a therapeutic small molecule if an appropriate delivery system is available, particularly for liver fibrosis caused by hepatitis B virus infection. Key Words: MicroRNA, miR-302, PAK5, HBV, Liver fibrosis, Cirrhosis.